1993
DOI: 10.1073/pnas.90.16.7485
|View full text |Cite
|
Sign up to set email alerts
|

Photochemically induced cataracts in rat lenses can be prevented by AL-3823A, a glutathione peroxidase mimic.

Abstract: Oiddatve stress is known to cause cataracts In lens culture systems and is believed to be an important factor contributing to human cataracts. In this communication, it is demonstrated that cataract development of cultured rat lenses produced as a result of photochemkaily induced oxidation in a 4% oxygen atmosphere imilar to the native environment ofthe lens can be blocked by the ttion metal complex AL-3823A. In this system, riboflavin is added to the medium as a photosensitizer. AL-3823A acts primarily as a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 17 publications
(24 reference statements)
0
20
0
Order By: Relevance
“…The control lenses were incubated in the same medium but without exposure to light. Previous studies have shown that the photochemical reaction used generates mainly superoxide anion radical and H 2 O 2 and to a much lesser extent hydroxyl radical (41). In addition, development of opacity in lenses following photochemical stress could be prevented by the addition of exogenous catalase, suggesting the pathogenic role of H 2 O 2 in this model of cataract (42).…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…The control lenses were incubated in the same medium but without exposure to light. Previous studies have shown that the photochemical reaction used generates mainly superoxide anion radical and H 2 O 2 and to a much lesser extent hydroxyl radical (41). In addition, development of opacity in lenses following photochemical stress could be prevented by the addition of exogenous catalase, suggesting the pathogenic role of H 2 O 2 in this model of cataract (42).…”
Section: Methodsmentioning
confidence: 75%
“…Exposure of Lens to Oxidative Stress Generated by Photochemical Reaction-The method for quantifying damage in animal lens following exposure to photochemically induced oxidative stress has been previously described (41)(42)(43). Briefly, lenses were removed from the eyes of Cat ϩ/ϩ and Cat Ϫ/Ϫ mice immediately following sacrifice.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies with glutathione peroxidase mimics [37,38] have also shown that they are capable of assist ing in the protection against free radical-in duced damage to lenses. These experiments support the concept that the presence of a com pound that eliminates hydrogen peroxide is suf ficient to prevent cataract development during periods of oxidative stress.…”
Section: Lensmentioning
confidence: 99%
“…This finally results in cataract formation and blindness. Available reports suggest that elimination of H 2 O 2 by antioxidants can prevent cataract formation in cultured animal lenses (Spector et al, 1993) as well as in rabbit lens epithelial cells (Reddan et al, 1993).…”
Section: Resultsmentioning
confidence: 99%